Learning to read the beginning Indonesian language using flashcard media for children with mental disabilities in public schools - Hetty Purnamasari; Nensy Megawati Simanjutak; I. Imayah; Ninik Mardiana; Wan Suraya Wan Nik (Research and Development in Education (RaDEn), 2025)
Children with intellectual disabilities are children who experience delays in development below average so that they need more special services and assistance. In their language development, it is marked by children who ask a lot of questions about something that is not yet known. The vocabulary of children with intellectual disabilities reaches 3000-5000 words. They like to imitate other people's actions, seek attention, retell stories, children's social development begins to learn to recognize. This study uses a quantitative approach of the pre-experimental type with the one group-pretest-posttest design. The environment by playing together or making groups when playing, their cognitive development is concrete and focused. Early reading learning in elementary schools aims for students to master the writing system so that they can read and understand using the system. Flash cards are picture cards equipped with written words that match the picture, making it easier for children to remember them.